Influence and involvement of support people in adolescent and young adult HIV testing. Issue 1 (2nd January 2019) - Neary, Jillian; Wagner, Anjuli D.; Mugo, Cyrus; Mutiti, Peter M.; Bukusi, David; John-Stewart, Grace C.; Wamalwa, Dalton C.; Kohler, Pamela K.; Slyker, Jennifer A.
ABSTRACT: HIV incidence and mortality are high among adolescents and young adults (AYA) in sub-Saharan Africa, but testing rates are low. Understanding how support people (SP), such as peers, partners, or parents, influence AYA may improve HIV testing uptake. AYA aged 14–24 seeking HIV testing at a referral hospital in Nairobi, Kenya completed a post-test survey assessing the role of SP. Among 1062 AYA, median age was 21. Overall, 12% reported their decision to test was influenced by a parent, 20% by a partner, and 22% by a peer. Young adults (20–24 years old) were more likely than adolescents (14–19 years old) to be influenced to test by partners (23% vs. 12%, p < .001), and less likely by parents (6.6% vs. 27%, p < .001), healthcare workers (11% vs. 16%, p < .05), or counselors (9.4% vs. 19%, p < .001). Half of AYA were accompanied for testing (9.9% with parent, 10% partner, 23% peer, 4.3% others, and 2.1% multiple types). Young adults were more likely than adolescents to present alone (58% vs. 32%, p < .001) or with a partner (12% vs. 6.7%, p < .05), and less likely with a parent (1.6% vs. 31%, p < .001). Similar proportions of adolescents and young adults came with a peer or in a group. Correlates of presenting with SP included: younger age (aRR = 1.55 [95%CI = 1.30–1.85]), female sex (aRR = 1.45 [95%CI = 1.21–1.73]), and school enrollment (aRR = 1.41 [95%CI = 1.05–1.88]). SP play an important role in AYAs' HIV testing and varies with age. Leveraging SP may promote uptake of HIV testing and subsequent linkage care for AYA.